Tension-softening behavior of UHPFRC based on fracture energy. (April 2022) - Lee, Seok-In; Kim, Jae-Hyun; Han, Sun-Jin; Jeong, Hoseong; Seo, Soo-Yeon; Su Kim, Kang
Highlights: This study analyzed the tensile behavior of UHPFRC based on fracture energy. Test variables were the size of specimens and the volume fraction of steel fibers. Inverse analysis and genetic algorithm were applied to obtain the fracture energy. Two evaluation factors were proposed to estimate the contribution of steel fibers. Abstract: In this study, a three-point bending test is performed on an ultra-high-performance fiber-reinforced concrete (UHPFRC) to determine its tensile performance based on the volume fraction of steel fibers ( v f ) and member depth as test variables. Based on the bending test results, the overall tensile behavior ( σ - ε relationship) of each specimen is derived from an inverse analysis and optimization using a genetic algorithm, and changes in the behavior are analyzed comprehensively based on key variables. In addition, evaluation factors ( η 1 and η 2 ) that can quantitatively represent the contribution of steel fibers on the fracture energy of the UHPFRC are proposed based on a comparative analysis between fracture energies calculated using the σ - ε relationship and conventional fracture energies. For specimens in which v f is less than 2%, the fracture energy enhanced by steel fibers decreases as the member depth increases, and the values of the evaluation factors ( η 1 and η 2 ) are maximum at v f 2.0%